Study on pyrolysis characteristics of lump coal in the context of underground coal gasification. (15th December 2021) - Xin, Lin; An, Mingyu; Feng, Mingze; Li, Kaixuan; Cheng, Weimin; Liu, Weitao; Hu, Xiangming; Wang, Zhigang; Han, Limin
Abstract: Coal reaction in dry distillation zone, as an essential step in underground coal gasification (UCG), is of great significance to be studied about its characteristics in a comprehensive way. This study simulated the pyrolysis process of lump coal in UCG tunnel in a laboratory. Lump coal samples were heated in nitrogen environment at 200–600 °C. The functional groups, pore structure, and microcrystalline structure of coal samples were analyzed by Fourier transform infrared spectrometer, scanning electron microscope, and X-ray diffractometer. The results showed that, as final pyrolysis temperature increased, the contents of hydroxyl, aliphatic, and aromatic groups all showed decreasing trends. The escalation of CHar /CC and CH2 /CH3 implied that the condensation degree of aromatic structure and the branching degree of fatty chain increased. With the temperature increasing, volatile substances such as CO2 and CH4 were released. Coal samples had higher porosity and gradually turned hollowed. The d 002 (Interlinear Spacing of Microcrystalline) of the coal sample decreased, L c (final stacking height) increased and L c /d 002 (stacking layer numbers) decreased, indicating that the crystal structure of coal samples tended to be more disordered. Highlights: Lump pyrolysis of UCG was simulated under a nitrogen atmosphere. FTIR, XRD and SEM tests was carried out to analyze structure characteristics. Oxygen-containing groups and aromatic groups decreases with temperature.